LGR4 and LGR6 are differentially expressed and of putative tumor biological significance in gastric carcinoma - Steffen, Jan Simon; Ebert, Matthias (Virchows Archiv, 2012)
Gastric cancer (GC) is one of the most common causes of cancer-related deaths worldwide. We investigated the differential expression and putative tumor biological significance of five G-protein-coupled receptors (GPCRs) in GC, i.e., LGR4, LGR6, GPR34, GPR160, and GPR171. Based on our previous microarray analyses, we identified five candidate genes in human GC samples. Real-time RT-PCR was carried out to validate their expression in malignant and non-malignant tissues on an independent collective comprising 32 GC patients with and without lymph node metastases. Selected protein targets LGR4 and LGR6 were further validated on paraffin-embedded sections of ten intestinal and ten poorly cohesive (diffuse)-type GCs and their corresponding non-malignant tissue using immunohistochemistry. Additionally, the putative tumor biological significance of LGR4 and LGR6 was studied using tissue microarrays obtained from a cohort of 481 GC patients. On transcriptional level, GPR34, GPR160, and GPR171 were not differentially expressed in GC compared with non-neoplastic mucosa. LGR4 and LGR6 were up-regulated on transcriptional (real-time RT-PCR) and translational (immunohistochemistry) levels in GC. Furthermore, in tissue microarray analysis, LGR6 expression was significantly associated with local tumor growth (T-category; p = 0.04) and correlated with patient survival. LGR4 expression was significantly correlated with nodal spread (N-category; p = 0.025). Our systematic analysis indicates that LGR4 and LGR6 may play a role in GC biology. Future studies will have to demonstrate whether these are also putative diagnostic, prognostic, and/or therapeutic targets for GC.